Alliin Induces Reconstitution of Testes Damaged by Estrogen Overstimulation by Regulating Apoptosis - Dae-Seung Kim; Min-Jee Oh; Sang-Hwan Kim (Current Issues in Molecular Biology)
We analyzed the effect of alliin on the recovery of mouse testicular function and structure following estradiol treatment as well as on apoptosis regulation. During the cultivation of testicular cells, high-concentration estradiol suppressed Casp-3; PCNA, mTOR, and PI3K signaling increased; and cell proliferation in the testes was abnormally increased. Therefore, estradiol treatment increased the proportion of abnormal cells. The estradiol and 2.5 μM of alliin treatment increased Casp-3 levels and suppressed Bcl-2, PCNA, mTOR, and PI3K expression. Additionally, treatment with estradiol caused tissue loss. Furthermore, Ca2+ deposition decreased, TNF-r protein expression increased, and the levels of other protein markers of cell survival and death decreased. Tissue recovery and restoration of the testes occurred after alliin treatment; the gene expression of cell survival and death markers, except for TNF-r, increased with increasing Ca2+ deposition. Cell proliferation and tissue reorganization may correlate with an increased signal of intrinsic apoptosis owing to increased Ca2+ deposition. Therefore, treatment with alliin may regulate the apoptosis of cells with normal or abnormal signal transduction and help to revert testicular dysfunction.